Information seeking behaviour of undergraduate students in the humanities in three universities in Nigeria - Emmanuel E. Baro (South African Journal of Libraries and Information Science, 2010)
The purpose of this study is to establish the information needs, sources, and the information searching strategies of undergraduate students. The study adopted a descriptive survey method. The study covers 100-400 level undergraduate students in history in the humanities in three universities in the South-South geo-political zone of Nigeria. A sample size of 259 was used for the study. Random sampling technique was used in selecting the sampled respondents. The study opted the use of questionnaires, interviews and observation methods. It emerged that the undergraduate students use sources such as textbooks, journals, Internet, and rely heavily on human resources for information. The study also revealed that undergraduate students use search strategies such as starting, chaining, browsing, differentiating, monitoring and extracting. There is a significant difference between male and female students in the sources they use in obtaining information in the humanities and in their search strategies. Findings will enable library administrators and university management to see the need to integrate information literacy courses into the school curriculum. Also to enable librarians to intensify their efforts to educate students about the information environment rather than simply providing the knowledge of how to use specific tools.